PENGARUH FINANCIAL BEHAVIOR DAN PERILAKU PENEMUAN INFORMASI ORANG TUA TERHADAP PEMILIHAN TIPE SEKOLAH DASAR - RAHMA IMANDA NUR KHASANAH; Muhtarom, Taufik (Jurnal Gentala Pendidikan Dasar, 2025)
Choosing an elementary school is not easy for parents, there are many factors for parents to consider when choosing a school for their child. Currently, many parents do not prepare education funds and have little information on school choices. Therefore, the purpose of this study is to determine the influence of financial behavior and parental information discovery behavior on the selection of elementary school types. This study uses a type of quantitative survey research with a population of 145 parents and 108 parents were taken as a research sample. The research data was obtained from parents of kindergarten B children in group eight of Kasihan District, Bantul Regency, Yogyakarta. Data collection was conducted using a questionnaire of 54 statements with a likert scale and an intensity scale. Data analysis used multiple regression test technique. The results of the T test research obtained a sig. value of 0.00 and a T value calculated -4.819, so financial behavior has a significant influence on the selection of the type of elementary school. The value of sig. 0.014 and a T value of 2.492, then information discovery behavior has a significant influence on the selection of elementary school types. Then the results of the F test were obtained with a sig value. 0.00 and F count 12.872, then financial behavior and behavior of finding parental information have a significant effect on the selection of the type of elementary school. This study shows the need for parents of students to prepare children's education costs, schools providing websites/social media, and active information discovery behavior.